A new approach to P-doping and the observation of efficiency enhancement in InP/InGaAs quantum well solar cells - Zacnariou, A. (Institutional Knowledge at Singapore Management University, 1996)
The authors report on lattice matched InP/In/sub x/Ga/sub 1-x/As multiple quantum well solar cells (QWSCs). An alternative method of p-doping is used, which allows the dopant to diffuse from a highly doped InGaAs cap into an underlying InP layer which has no deliberate doping. They discuss an important experimental technique, the measurement of the monochromatic photocurrent as a function of bias, used to test this approach to p-doping of InP. A model has been developed and theoretical fits of the spectral response (SR) of several multiple quantum well (MQW) samples are shown. They present results that show the enhancement of the short-circuit current (I/sub SC/) over a comparable InP cell and the enhancement of the open-circuit voltage (V/sub OC/) over an InP/InGaAs double heterostructure. This is the first observation of QWSC efficiency enhancement over comparable conventional solar cells made from the well material alone.